Solid electrolyte, solid electrolyte layer and solid electrolyte battery

A solid electrolyte with a specific composition and crystal structure addresses the issue of low ionic conductivity in conventional electrolytes, enhancing discharge capacity and reducing resistance in solid electrolyte batteries.

JP7618556B2Active Publication Date: 2025-01-21TDK CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021537256
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-07
Filing Date
2020-07-29
Publication Date
2025-01-21
Estimated Expiration
2040-07-29

AI Technical Summary

Technical Problem

Conventional solid electrolytes exhibit insufficient ionic conductivity, limiting the discharge capacity of solid electrolyte batteries.

Method used

A solid electrolyte composed of a compound containing an alkali metal element, a tetravalent metal element, and a halogen element, with a specific crystal structure confirmed by X-ray diffraction, which enhances ionic conductivity through the formation of mobile ion pathways.

Benefits of technology

The proposed solid electrolyte exhibits high ionic conductivity, leading to improved discharge capacity and reduced internal resistance in solid electrolyte batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618556000002
    Figure 0007618556000002
  • Figure 0007618556000003
    Figure 0007618556000003
  • Figure 0007618556000004
    Figure 0007618556000004
Patent Text Reader

Abstract

A solid electrolyte according to one embodiment of the present invention comprises a compound that contains, as main elements, an alkali metal element, a tetravalent metal element and a halogen element; the compound has diffraction peaks at the positions of 2θ = 32.0° ± 0.5° and 2θ = 34.4° ± 0.5° with respect to the wavelength of a CuKα ray; and the ratio of the diffraction intensity IB of the peak having the highest diffraction intensity at 2θ = 34.4° ± 0.5° to the diffraction intensity IA of the peak having the highest diffraction intensity at 2θ = 32.0° ± 0.5°, namely IB / IA satisfies 0 < IB / IA ≤ 3.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte, a solid electrolyte layer, and a solid electrolyte battery. This application claims priority based on Japanese Patent Application No. 2019-145663 filed on August 7, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, electronics technology has made remarkable progress, and portable electronic devices have become smaller, lighter, thinner, and more multifunctional. Accordingly, there is a strong demand for batteries that serve as the power source for electronic devices to be smaller, lighter, thinner, and more reliable, and solid electrolyte batteries that use a solid electrolyte as the electrolyte have attracted attention.

[0003] Examples of methods for manufacturing solid electrolyte batteries include sintering and powder molding. In the sintering method, a negative electrode, a solid electrolyte layer, and a positive electrode are stacked, and then sintered to form a solid electrolyte battery. In the powder molding method, a negative electrode, a solid electrolyte layer, and a positive electrode are stacked, and then pressure is applied to form a solid electrolyte battery. The materials that can be used for the solid electrolyte layer vary depending on the manufacturing method. Known solid electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and complex hydride-based solid electrolytes (such as LiBH4).

[0004] In Patent Document 1, a positive electrode, a negative electrode, and a general formula Li 3-2X M X In 1-Y M´ Y L 6-Z L´ Z In the above general formula, M and M' are metal elements, and L and L' are halogen elements. X, Y, and Z independently satisfy 0≦X<1.5, 0≦Y<1, and 0≦Z≦6. The positive electrode includes a positive electrode layer containing a positive electrode active material including Li element, and a positive electrode current collector. The negative electrode includes a negative electrode layer containing a negative electrode active material, and a negative electrode current collector.

[0005] Patent Document 2 discloses a solid electrolyte material represented by the following compositional formula (1). Li 6-3Z Y Z X6···Formula (1) Here, 0 < Z < 2 is satisfied, and X is Cl or Br. Further, Patent Document 2 describes a battery in which at least one of the negative electrode and the positive electrode contains the solid electrolyte material.

[0006] Patent Document 3 describes an all-solid-state battery including an electrode active material layer having a first solid electrolyte material and a second solid electrolyte material. The first solid electrolyte material is a single-phase electron-ion mixed conductor, and is a material that is in contact with the active material and has an anion component different from the anion component of the active material. The second solid electrolyte material is in contact with the first solid electrolyte material, has the same anion component as the first solid electrolyte material, and is an ion conductor having no electron conductivity. The first solid electrolyte material is Li2ZrS3, and in X-ray diffraction measurement using CuKα rays, it has peaks at positions of 2θ = 34.2° ± 0.5° and 2θ = 31.4° ± 0.5°. When the diffraction intensity of the peak of Li2ZrS3 at 2θ = 34.2° ± 0.5° of the first solid electrolyte material is IA and the diffraction intensity of the peak of ZrO2 at 2θ = 31.4° ± 0.5° is IB, the value of IB / IA is 0.1 or less.

Prior Art Documents

Patent Documents

[0007]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of the Invention

Problems to be Solved by the Invention

[0008] However, the solid electrolytes described in Patent Documents 1 to 3 all had insufficient ionic conductivity. For this reason, sufficient discharge capacity could not be obtained with conventional solid electrolyte batteries.

[0009] The present invention has been made in view of the above problems, and an object thereof is to provide a solid electrolyte, a solid electrolyte layer, and a solid electrolyte battery having improved ionic conductivity.

Means for Solving the Problems

[0010] The present inventor has intensively studied to solve the above problems. As a result, it has been found that a solid electrolyte having a compound containing an alkali metal element, a tetravalent metal element, and a halogen element as a main element and having a characteristic structure confirmed in the measurement result of X-ray diffraction (XRD) has high ionic conductivity of mobile ions. That is, in order to solve the above problems, the following means are provided.

[0011] (1) The solid electrolyte according to the first aspect has a compound containing an alkali metal element, a tetravalent metal element, and a halogen element as a main element, and the compound has diffraction peaks at positions of 2θ = 32.0° ± 0.5° and 2θ = 34.4° ± 0.5° with respect to the wavelength of CuKα ray, and the ratio IB / IA of the diffraction intensity IB of the peak having the strongest diffraction intensity at 2θ = 34.4° ± 0.5° to the diffraction intensity IA of the peak having the strongest diffraction intensity at 2θ = 32.0° ± 0.5° satisfies 0 < IB / IA ≦ 3.

[0012] (2) The solid electrolyte according to the second aspect has a compound containing an alkali metal element, a tetravalent metal element, and a halogen element as a main element, and the compound has diffraction peaks at positions of 2θ = 32.0° ± 0.5° and 2θ = 30.0° ± 0.5° with respect to the wavelength of CuKα ray, and the ratio IC / IA of the diffraction intensity IC of the peak having the strongest diffraction intensity at 2θ = 30.0° ± 0.5° to the diffraction intensity IA of the peak having the strongest diffraction intensity at 2θ = 32.0° ± 0.5° satisfies 0 < IC / IA ≦ 2.

[0013] (3) The compound of the solid electrolyte according to the above embodiment may have diffraction peaks at 2θ=16.1°±0.5°, 2θ=41.7°±0.5°, and 2θ=49.9°±0.5° with respect to the wavelength of CuKα radiation.

[0014] (4) The compound of the solid electrolyte according to the above embodiment may have diffraction peaks at the following positions relative to the wavelength of CuKα radiation: 2θ=43.7°±0.5°, 2θ=45.0°±0.5°, 2θ=54.2°±0.5°, 2θ=59.1°±0.5°, 2θ=60.5°±0.5°, and 2θ=62.2°±0.5°.

[0015] (5) The compound of the solid electrolyte according to the above embodiment may have diffraction peaks at θ=30.0°±0.5° and 2θ=34.4°±0.5° with respect to the wavelength of CuKα radiation.

[0016] (6) In the solid electrolyte according to the above aspect, the tetravalent metal element may be one or more elements selected from the group consisting of Zr, Hf, Ti, Sn, and Ge.

[0017] (7) In the solid electrolyte according to the above aspect, the compound has the composition formula Li 2+a M b Zr 1+c Cl 6+d and satisfying -1.5≦a≦1.5, 0≦b≦1.5, -0.7≦c≦0.2, and -0.2≦d≦0.2, where M may be one or more elements selected from Al, Y, Ca, Nb, and Mg.

[0018] (8) A solid electrolyte layer according to a third aspect has the solid electrolyte according to the above aspect.

[0019] (9) A solid electrolyte battery according to a fourth aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, and at least one of the positive electrode, the negative electrode, and the solid electrolyte layer contains the solid electrolyte according to the above aspect.

[0020] (10) A solid electrolyte battery according to a fifth aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, the solid electrolyte layer including the solid electrolyte according to the above aspect. Effect of the Invention

[0021] The solid electrolyte, solid electrolyte layer, and solid electrolyte battery according to the above aspects have high ionic conductivity. [Brief description of the drawings]

[0022] [Figure 1] 1 is a schematic cross-sectional view of a solid electrolyte battery according to an embodiment of the present invention. [Diagram 2] This is the background X-ray diffraction result. [Diagram 3] 1 shows X-ray diffraction results of solid electrolytes according to Examples 1, 9, and 10, and Comparative Example 2. [Figure 4] 2 is an enlarged view of a main portion of the X-ray diffraction results of the solid electrolytes according to Examples 1, 9, and 10, and Comparative Example 2. FIG. [Diagram 5] 1 shows X-ray diffraction results of solid electrolytes according to Examples 1, 2, and 5, and Comparative Example 1. [Figure 6] 1 shows the results of X-ray diffraction of the solid electrolytes according to Examples 1, 14, and 16. [Figure 7] 1 shows the results of X-ray diffraction of the solid electrolytes according to Examples 1, 22, and 29. [Figure 8] 1 shows the results of X-ray diffraction of the solid electrolytes according to Examples 10 and 32. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present embodiment will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.

[0024] [Solid electrolyte battery] Fig. 1 is a cross-sectional schematic diagram of a solid electrolyte battery according to a first embodiment. As shown in Fig. 1, a solid electrolyte battery 10 has a positive electrode 1, a negative electrode 2, and a solid electrolyte layer 3. The solid electrolyte layer 3 is sandwiched between the positive electrode 1 and the negative electrode 2. External terminals are connected to the positive electrode 1 and the negative electrode 2, and the battery is electrically connected to the outside. The all-solid-state battery is one aspect of the solid electrolyte battery.

[0025] The solid electrolyte battery 10 is charged or discharged by the exchange of ions between the positive electrode 1 and the negative electrode 2 via the solid electrolyte layer 3. The solid electrolyte battery 10 may be a laminate in which the positive electrode 1, the negative electrode 2, and the solid electrolyte layer 3 are laminated, or a wound body in which the laminate is wound. The solid electrolyte battery is used, for example, in laminate batteries, square batteries, cylindrical batteries, coin batteries, button batteries, etc. The solid electrolyte battery may also be of an injection type in which the solid electrolyte layer 3 is dissolved or dispersed in a solvent.

[0026] "Solid electrolyte layer" The solid electrolyte layer 3 includes a solid electrolyte.

[0027] The solid electrolyte contains a compound containing an alkali metal element, a tetravalent metal element, and a halogen element as main elements, and hereinafter, this compound is referred to as a halogenated compound.

[0028] When a solid electrolyte contains a compound with this composition, the presence of a tetravalent metal element weakens the binding of the alkali metal by the halogen element. As a result, an ion conduction path is formed inside the solid electrolyte, making it easier for the alkali metal (mobile ion) to move. In addition, the tetravalent metal element and the halogen element form a space within the crystal structure through which the mobile ions can conduct. The combination of these effects improves the ionic conductivity of the solid electrolyte.

[0029] Here, "containing as main elements" means that these elements are contained as basic elements constituting the compound. For example, the elements forming the basic skeleton of the halogenated compound are an alkali metal element, a tetravalent metal element, and a halogen element. The halogenated compound may be composed of an alkali metal element, a tetravalent metal element, and a halogen element. The halogenated compound may also be a compound in which the alkali metal element, the tetravalent metal element, and the halogen element are partially substituted. The solid electrolyte layer mainly contains, for example, a halogenated compound. "Mainly" means that the proportion of the halogenated compound among the compounds contained in the solid electrolyte layer is the highest. The solid electrolyte layer may be composed of a halogenated compound.

[0030] The alkali metal element contained in the halogenated compound is, for example, any one of Li, K, and Na. The alkali metal element contained in the halogenated compound is preferably Li. The alkali metal element is a mobile ion that moves within the solid electrolyte layer 3 in the solid electrolyte battery 10. The mobile ion is an ion that is transferred between the positive electrode 1 and the negative electrode 2, and is, for example, a Li ion.

[0031] The tetravalent metal element contained in the halogenated compound is, for example, one or more elements selected from the group consisting of Zr, Hf, Ti, Sn, and Ge. The tetravalent metal element contained in the halogenated compound is preferably Zr. Zr is low cost, light weight, and enhances the stability of the battery.

[0032] The halogen element contained in the halogenated compound is, for example, one or more elements selected from the group consisting of F, Cl, Br, and I. The halogen element contained in the halogenated compound is preferably Cl.

[0033] The halogenated compound may contain elements other than alkali metal elements, tetravalent metal elements, and halogen elements. For example, the halogenated compound may contain monovalent to hexavalent metal elements (excluding tetravalent metal elements) other than alkali metal elements, tetravalent metal elements, and halogen elements. The monovalent metal elements contained in the halogenated compound are, for example, Ag and Au. The divalent metal elements contained in the halogenated compound are, for example, Mg, Ca, Sr, Ba, Cu, Pb, and Sn. The trivalent metal elements contained in the halogenated compound are, for example, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Bi, In, Sb, and Nb. The pentavalent metal element contained in the halogenated compound is, for example, Ta. The hexavalent metal element contained in the halogenated compound is, for example, W.

[0034] The monovalent to hexavalent metal elements (excluding tetravalent metal elements) contained in the halogenated compound are substituted with, for example, at least one of a tetravalent metal element and an alkali metal element.

[0035] The halogenated compound may be, for example, a compound having the formula Li 2+a M b Zr 1+c Cl 6+d The above composition formula satisfies -1.5≦a≦1.5, 0≦b≦1.5, -0.7≦c≦0.2, and -0.2≦d≦0.2.

[0036] M is an element substituting the Zr site or Li site. M is, for example, the above monovalent to hexavalent metal elements (excluding tetravalent metal elements). M is preferably one or more elements selected from Al, Y, Ca, Nb, and Mg. The following is a definition of each subscript in the above composition formula. That is, the case where the tetravalent metal element is Zr is described as an example.

[0037] When M is a monovalent element substituting a Zr site, it is preferable that the above composition formula further satisfies a=3b, 0≦b≦0.5.

[0038] When M is a monovalent element substituting the Li site, it is preferable that the above composition formula further satisfies a=-b, 0≦b≦0.5.

[0039] When M is a divalent element substituting the Zr site, it is preferable that the above composition formula further satisfies a=2b, 0≦b≦0.5. It is preferable that M is at least one of Mg and Ca.

[0040] When M is a divalent element substituting the Li site, the above composition formula preferably further satisfies a=-2b, 0≦b≦0.5. M is preferably at least one of Mg and Ca.

[0041] When M is a trivalent element substituting the Zr site, the above composition formula preferably further satisfies a=b, 0≦b≦0.5. M is preferably at least one element selected from the group consisting of Al, Y, and Nb.

[0042] When M is a trivalent element substituting the Li site, the above composition formula preferably further satisfies a=-3b, 0≦b≦0.5. M is preferably at least one element selected from the group consisting of Al, Y, and Nb.

[0043] When M is a pentavalent element substituting the Zr site, it is preferable that the above composition formula further satisfies a=-b, 0≦b≦0.5.

[0044] When M is a pentavalent element substituting the Li site, it is preferable that the above composition formula further satisfies a=-5b, 0≦b<0.4.

[0045] When M is a hexavalent element substituting the Zr site, it is preferable that the above composition formula further satisfies a=-2b, 0≦b≦0.5.

[0046] When M is a hexavalent element substituting the Li site, it is preferable that the above composition formula further satisfies a=-6b, 0≦b≦1 / 3.

[0047] By substituting a part of the tetravalent metal element with at least one element selected from the group consisting of monovalent to trivalent elements, the number of mobile ion carriers can be increased to compensate for the decrease in the cations, thereby improving the ionic conductivity of the solid electrolyte.

[0048] When a part of a tetravalent metal element is replaced with at least one element selected from the group consisting of other tetravalent elements, the binding of the alkali metal by the halogen element is weakened, and the alkali metal (mobile ion) becomes more mobile, which improves the ionic conductivity of the solid electrolyte.

[0049] When a part of the tetravalent metal element is replaced with at least one element selected from the group consisting of pentavalent and hexavalent elements, the number of mobile ions of the increased cations is decreased, and the number of vacancies in the crystal structure is increased, resulting in improved ionic conductivity of the solid electrolyte.

[0050] At least a part of the solid electrolyte is crystalline. For example, a part of the halogenated compound is crystalline. When a part of the solid electrolyte is crystalline, a diffraction peak is confirmed when X-ray diffraction measurement is performed using CuKα rays. The solid electrolyte has a diffraction peak at 2θ=32.0°±0.5° and 2θ=34.4°±0.5° with respect to the wavelength of CuKα rays. The solid electrolyte may have a diffraction peak at 2θ=32.0°±0.5° and 2θ=30.0°±0.5° with respect to the wavelength of CuKα rays. Having a diffraction peak at a predetermined position with respect to CuKα rays means, for example, that diffracted light generated when light with a wavelength of CuKα rays is incident on the solid electrolyte has a diffraction peak at a predetermined position.

[0051] The solid electrolyte preferably has diffraction peaks at positions of 2θ = 16.1° ± 0.5°, 2θ = 41.7° ± 0.5°, and 2θ = 49.9 ± 0.5° with respect to the CuKα ray. Further, the solid electrolyte more preferably has diffraction peaks at positions of 2θ = 43.7 ± 0.5°, 45.0 ± 0.5°, 2θ = 54.2° ± 0.5°, 2θ = 59.1° ± 0.5°, 2θ = 60.5° ± 0.5°, and 2θ = 62.2° ± 0.5° with respect to the CuKα ray. When the solid electrolyte has the above diffraction peaks, an ion conduction path is secured within the crystal structure, and the ion conductivity is improved.

[0052] Furthermore, the solid electrolyte more preferably has diffraction peaks at positions of 2θ = 30.0° ± 0.5° and 2θ = 34.4° ± 0.5° with respect to the CuKα ray. These diffraction peaks are, for example, diffraction peaks associated with a halogenated compound. When the above diffraction peaks are confirmed, an ion conduction path is more secured within the crystal structure, and the ion conductivity is improved.

[0053] Also, the diffraction intensity IA of the diffraction peak at 2θ = 32.0° ± 0.5° and the diffraction intensity IB of the diffraction peak at 2θ = 34.4° ± 0.5° preferably satisfy 0 < IB / IA ≦ 3, and more preferably satisfy 0 < IB / IA ≦ 2. By setting the crystal structure to satisfy such specific range values, a path with high partial ion conductivity is formed within the crystal structure, and the ion conductivity is further improved.

[0054] Also, the diffraction intensity IA of the diffraction peak at 2θ = 32.0° ± 0.5° and the diffraction intensity IC of the diffraction peak at 2θ = 30.0° ± 0.5° preferably satisfy 0 < IC / IA ≦ 2, and more preferably satisfy 0 < IC / IA ≦ 1.5. By setting the crystal structure to satisfy such specific range values, a path with high partial ion conductivity is formed within the crystal structure, and the ion conductivity is further improved.

[0055] The solid electrolyte layer 3 may contain a material other than a solid electrolyte. The solid electrolyte layer 3 may contain, for example, an oxide or halide of the above-mentioned alkali metal element, an oxide or halide of the above-mentioned tetravalent metal element, or an oxide or halide of the above-mentioned M element. The solid electrolyte layer 3 preferably contains 0.1 mass % or more and 1.0 mass % or less of these materials. These materials increase the electrical insulation in the solid electrolyte layer 3 and improve the self-discharge of the solid electrolyte battery.

[0056] The solid electrolyte layer 3 may include a binder. The solid electrolyte layer 3 may include, for example, fluororesins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), cellulose, styrene-butadiene rubber, ethylene-propylene rubber, imide resins such as polyimide resins and polyamide-imide resins, ion-conductive polymers, and the like. The ion-conductive polymer is, for example, a compound obtained by compounding a monomer of a polymer compound (polyether polymer compounds such as polyethylene oxide and polypropylene oxide, polyphosphazene, and the like) with a lithium salt such as LiClO4, LiBF4, LiPF6, LiTFSI, or an alkali metal salt mainly composed of lithium. The content of the binder is preferably 0.1% by volume or more and 30% by volume or less of the entire solid electrolyte layer 3. The binder helps to maintain good bonding between the solid electrolytes of the solid electrolyte layer 3, prevents the occurrence of cracks between the solid electrolytes, and suppresses a decrease in ion conductivity and an increase in grain boundary resistance.

[0057] "Positive electrode" As shown in FIG. 1, the positive electrode 1 has, for example, a positive electrode current collector 1A and a positive electrode active material layer 1B containing a positive electrode active material.

[0058] (Positive electrode current collector) The positive electrode current collector 1A preferably has high electrical conductivity. For example, metals such as silver, palladium, gold, platinum, aluminum, copper, nickel, titanium, and stainless steel, and alloys thereof, or conductive resins can be used. The positive electrode current collector 1A may be in the form of powder, foil, punching, or expandable.

[0059] (Positive electrode active material layer) The positive electrode active material layer 1B is formed on one or both sides of the positive electrode current collector 1A. The positive electrode active material layer 1B contains a positive electrode active material and may contain, if necessary, a conductive assistant, a binder, and the above-mentioned solid electrolyte.

[0060] (Positive electrode active material) The positive electrode active material contained in the positive electrode active material layer 1B is, for example, a lithium-containing transition metal oxide, a transition metal fluoride, a polyanion, a transition metal sulfide, a transition metal oxyfluoride, a transition metal oxysulfide, or a transition metal oxynitride.

[0061] The positive electrode active material is not particularly limited as long as it can reversibly proceed with the release and occlusion of lithium ions and the desorption and insertion of lithium ions, and a positive electrode active material used in a known lithium-ion secondary battery can be used. The positive electrode active material is, for example, lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganese spinel (LiMn2O4), and the general formula: LiNi x Co y Mn z M a O2 (x + y + z + a = 1, 0 ≦ x ≦ 1, 0 ≦ y ≦ 1, 0 ≦ z ≦ 1, 0 ≦ a ≦ 1, M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), a lithium vanadium compound (LiV2O5, Li3V2(PO4)3, LiVOPO4), an olivine-type LiMPO4 (where M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, V, Nb, Ti, Al, Zr), lithium titanate (Li4Ti5O 12 )), LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1), etc., are composite metal oxides.

[0062] In addition, if a negative electrode active material in which the negative electrode is previously doped with metallic lithium or lithium ions is arranged, a positive electrode active material that does not contain lithium can also be used by starting the battery from discharge. Examples of such positive electrode active materials include lithium-free metal oxides (such as MnO2 and V2O5), lithium-free metal sulfides (such as MoS2), and lithium-free fluorides (such as FeF3 and VF3).

[0063] "Negative electrode" As shown in FIG. 1, the negative electrode 2 has, for example, a negative electrode current collector 2A and a negative electrode active material layer 2B containing a negative electrode active material.

[0064] (Negative electrode current collector) The negative electrode current collector 2A preferably has high conductivity. For example, it is preferable to use metals such as silver, palladium, gold, platinum, aluminum, copper, nickel, stainless steel, iron and their alloys, or a conductive resin. The negative electrode current collector 2A may be in the form of powder, foil, punching, or expansion.

[0065] (Negative electrode active material layer) The negative electrode active material layer 2B is formed on one or both sides of the negative electrode current collector 2A. The negative electrode active material layer 2B contains a negative electrode active material and may contain, if necessary, a conductive assistant, a binder, and the above-described solid electrolyte.

[0066] (Negative electrode active material) The negative electrode active material contained in the negative electrode active material layer 2B may be any compound capable of occluding and releasing mobile ions, and a negative electrode active material used in a known lithium-ion secondary battery can be used. Examples of the negative electrode active material include simple alkali metals, alkali metal alloys, carbon materials such as graphite (natural graphite, artificial graphite), carbon nanotubes, graphitizable carbon, easily graphitizable carbon, and low-temperature fired carbon, metals such as aluminum, silicon, tin, germanium and their alloys that can combine with alkali metals such as metals, SiO x (0 < x < 2), oxides such as iron oxide and titanium oxide, tin dioxide, and lithium metal oxides such as lithium titanate (Li4Ti5O 12 ).

[0067] (Conductive assistant) The conductive assistant is not particularly limited as long as it improves the electronic conductivity of the positive electrode active material layer 1B and the negative electrode active material layer 2B, and a known conductive assistant can be used. Examples of the conductive assistant include carbon-based materials such as graphite, carbon black, graphene, and carbon nanotubes, metals such as gold, platinum, silver, palladium, aluminum, copper, nickel, stainless steel, and iron, conductive oxides such as ITO, and mixtures thereof. The conductive assistant may be in the form of powder or fiber.

[0068] (Binding material) The binder bonds positive electrode current collector 1A and positive electrode active material layer 1B, negative electrode current collector 2A and negative electrode active material layer 2B, positive electrode active material layer 1B, negative electrode active material layer 2B and solid electrolyte layer 3, various materials constituting positive electrode active material layer 1B, and various materials constituting negative electrode active material layer 2B.

[0069] The binder is preferably used within a range that does not impair the functions of the positive electrode active material layer 1B and the negative electrode active material layer 2B. The binder may be any material capable of the above-mentioned bonding, and examples thereof include fluororesins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). In addition to the above, examples of the binder may include cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, and the like. In addition, a conductive polymer having electronic conductivity or an ion conductive polymer having ionic conductivity may be used as the binder. Examples of the conductive polymer having electronic conductivity include polyacetylene. In this case, the binder also functions as a conductive additive particle, so that it is not necessary to add a conductive additive. As the ion-conductive polymer having ion conductivity, for example, one that conducts lithium ions can be used, and examples thereof include a composite of a monomer of a polymer compound (polyether polymer compounds such as polyethylene oxide and polypropylene oxide, polyphosphazene, etc.) and a lithium salt such as LiClO4, LiBF4, LiPF6, or an alkali metal salt mainly composed of lithium. Examples of the polymerization initiator used for the composite include a photopolymerization initiator or a thermal polymerization initiator that is compatible with the above-mentioned monomer. Properties required for the binder include oxidation / reduction resistance and good adhesiveness.

[0070] The content of the binder in the positive electrode active material layer 1B is not particularly limited, but is preferably 0.5 to 30% by volume of the positive electrode active material layer from the viewpoint of reducing the resistance of the positive electrode active material layer 1B.

[0071] The content of the binder in the negative electrode active material layer 2B is not particularly limited, but is preferably 0.5 to 30% by volume of the negative electrode active material layer from the viewpoint of reducing the resistance of the negative electrode active material layer 2B.

[0072] At least one of the positive electrode active material layer 1B, the negative electrode active material layer 2B, and the solid electrolyte layer 3 may contain a nonaqueous electrolyte solution, an ionic liquid, or a gel electrolyte for the purpose of improving the rate characteristic, which is one of the battery characteristics.

[0073] (Method of manufacturing solid electrolyte) A method for producing a solid electrolyte according to the present embodiment will be described. The solid electrolyte can be obtained by mixing and reacting raw material powders in a predetermined molar ratio to obtain a desired composition. There is no particular limit to the reaction method, and mechanochemical milling, sintering, melting, liquid phase, solid phase, and other methods can be used.

[0074] The solid electrolyte can be manufactured, for example, by mechanochemical milling. First, a planetary ball mill is prepared. The planetary ball mill is a device in which media (hard balls for accelerating grinding or mechanochemical reactions) and materials are placed in a dedicated container, and the device rotates and revolves around its axis to grind the materials or cause mechanochemical reactions between the materials.

[0075] Next, in a glove box with argon gas circulating, a dew point of -80°C or less, and an oxygen concentration of 1 ppm or less, a predetermined amount of zirconia balls are prepared in a zirconia container. Next, predetermined raw materials are prepared in a zirconia container in a predetermined molar ratio so as to obtain a desired composition, and the container is sealed with a zirconia lid. The raw materials may be powder or liquid. For example, titanium chloride (TiCl4) and tin chloride (SnCl4) are liquid at room temperature. Next, mechanochemical milling is performed at a predetermined rotation and revolution speed for a predetermined time, causing a mechanochemical reaction. This method makes it possible to obtain a powdered solid electrolyte made of a compound having a desired composition. The mechanochemical reaction can be controlled by heating or cooling the inside of the planetary ball mill device. Heating using a heater, water cooling, air cooling using a refrigerant, etc. can be used for this treatment.

[0076] Furthermore, when obtaining a sintered solid electrolyte, raw material powders containing predetermined elemental raw materials in a predetermined molar ratio are mixed, the mixed raw material powders are molded into a predetermined shape, and sintered in a vacuum or an inert gas atmosphere, thereby obtaining a sintered solid electrolyte.

[0077] (Method of manufacturing solid electrolyte battery) Next, a method for producing the solid electrolyte battery according to the present embodiment will be described. The solid electrolyte battery according to the present embodiment can be produced by a powder molding method.

[0078] (Powder molding method) First, a resin holder having a through hole in the center, a lower punch, and an upper punch are prepared. The diameter of the through hole of the resin holder is, for example, 10 mm, and the diameters of the lower punch and the upper punch are, for example, 9.99 mm. The lower punch is inserted from below the through hole of the resin holder, and a powdered solid electrolyte is poured from the opening side of the resin holder. Next, the upper punch is inserted on top of the poured powdered solid electrolyte, and the resin holder is placed on a press machine and pressed. The pressing pressure is, for example, 373 MPa. The powdered solid electrolyte is pressed by the upper punch and the lower punch in the resin holder to become a solid electrolyte layer 3.

[0079] Next, the upper punch is temporarily removed, and the material for the positive electrode active material layer is put on the upper punch side of the solid electrolyte layer 3. After that, the upper punch is inserted again, and pressing is performed. The pressing pressure is, for example, 373 MPa. The material for the positive electrode active material layer becomes the positive electrode active material layer 1B by pressing.

[0080] Next, the lower punch is temporarily removed, and the material for the negative electrode active material layer is placed on the lower punch side of the solid electrolyte layer 3. For example, the sample is turned upside down, and the material for the negative electrode active material layer is placed on the solid electrolyte layer 3. Thereafter, the lower punch is inserted again, and pressing is performed. The pressing pressure is, for example, 373 MPa. The material for the negative electrode active material layer becomes the negative electrode active material layer 1B by pressing. Through the above procedure, the solid electrolyte battery 10 of this embodiment is obtained.

[0081] If necessary, the solid electrolyte battery 10 may be a stainless steel disk and a Teflon (registered trademark) disk having four screw holes, stacked in the following order: stainless steel disk / Teflon (registered trademark) disk / solid-state battery 10 / Teflon (registered trademark) disk / stainless steel disk, and the four screws may be tightened. The solid electrolyte battery 10 may also be a similar mechanism having a shape retention function.

[0082] If necessary, the battery may be inserted into an exterior body (aluminum laminate bag) to which an externally drawn positive electrode terminal and an externally drawn negative electrode terminal are attached, and the screw on the side of the upper punch may be connected to the externally drawn positive electrode terminal in the exterior body and the screw on the side of the lower punch may be connected to the externally drawn negative electrode terminal in the exterior body with lead wires, and finally the opening of the exterior body may be heat sealed. The exterior body improves weather resistance.

[0083] Although the above-mentioned manufacturing method for the solid electrolyte battery 10 has been described by taking the powder molding method as an example, the battery may also be manufactured by a sheet molding method containing a resin.

[0084] For example, first, a solid electrolyte paste containing a powdered solid electrolyte is prepared. The prepared solid electrolyte paste is applied to a PET film or a fluorine-based resin film, dried, and peeled off to prepare a solid electrolyte layer 3. A positive electrode active material paste containing a positive electrode active material is applied to a positive electrode current collector 1A, and dried to form a positive electrode active material layer 1B, thereby preparing a positive electrode 1. A negative electrode 2 is prepared by applying a paste containing a negative electrode active material to a negative electrode current collector 2A, and dried to form a negative electrode mixture layer 2B.

[0085] Next, the solid electrolyte layer 3 is sandwiched between the positive electrode 1 and the negative electrode 2, and the whole is pressed and bonded together. Through the above steps, the solid electrolyte battery 10 of this embodiment is obtained.

[0086] The solid electrolyte battery of this embodiment may be one in which the pores of the positive electrode, separator, and negative electrode are filled with a solid electrolyte instead of the electrolytic solution of a conventional lithium ion secondary battery. Such a solid electrolyte battery can be manufactured, for example, by the following method. First, a solid electrolyte paint containing a powdered solid electrolyte and a solvent is prepared. An electrode body consisting of a positive electrode, a separator, and a negative electrode is also prepared. Then, the electrode body is impregnated with the solid electrolyte paint, and the solvent is removed. This results in a solid electrolyte battery in which the pores of the electrode body are filled with the solid electrolyte.

[0087] The solid electrolyte according to this embodiment has excellent ionic conductivity as shown in the examples described later. Therefore, the solid electrolyte battery according to this embodiment including the solid electrolyte according to this embodiment has a small internal resistance and a large discharge capacity.

[0088] In addition, solid electrolytes that have a specific diffraction peak in X-ray diffraction have excellent ionic conductivity. X-ray diffraction peaks occur when X-rays are incident on a plane in which atoms are regularly arranged, and the X-rays scattered by each atom interfere with each other and reinforce each other. In other words, the presence of a specific diffraction peak indicates that the orientation of part of the crystal is high and a specific arrangement plane is formed.

[0089] The solid electrolyte is responsible for the conduction of mobile ions between the positive electrode 1 and the negative electrode 2. The mobile ions conduct through the gaps between the atoms that make up the solid electrolyte. When a specific arrangement plane is formed in the solid electrolyte, a conduction path for the mobile ions is formed between the specific arrangement planes. The ionic conductivity of the solid electrolyte is improved when a conduction path for the mobile ions is formed. A solid electrolyte that has a specific diffraction peak in X-ray diffraction is considered to have a secured conduction path for the mobile ions and therefore improved ionic conductivity.

[0090] The solid electrolyte according to the present embodiment contains a tetravalent metal element as one of the constituent elements. For example, Patent Document 2 discloses a halogenated compound containing Li 6-3z Y z X6 (X is Cl or Br) is disclosed. 6-3z Y z In X6, Y is trivalent Y 3+ It exists as 6-coordinate Y 3+ The ionic radius of the tetravalent metal element contained in the solid electrolyte according to the present embodiment is 0.9 Å. 3+ For example, the ionic radius of 6-coordinate Zr 4+ is 0.72 Å, and the 6-coordinate Hf 4+ is 0.71 Å, and the 6-coordinate Ti 4+ is 0.605 Å, and the 6-coordinate Sn 4+is 0.69 Å. The quadruple ion is Y 3+ Therefore, the halogen ions (e.g., Cl) contained in the solid electrolyte have a smaller ionic radius and stronger electrostatic force. - ) are tightly bound by the tetravalent ions. When the halogen ions are bound by the tetravalent ions, the mobile ions are less susceptible to the electrical influence of the halogen ions and become more mobile, improving the mobile ion conductivity of the solid electrolyte. This also improves the mobile ion conductivity of the solid electrolyte layer.

[0091] Furthermore, when the solid electrolyte according to the present embodiment contains a monovalent to trivalent metal element, for example, a part of the tetravalent metal element is replaced with a monovalent to trivalent metal element. As a result, the amount of cations in the solid electrolyte is reduced. The charge neutrality of the solid electrolyte after the replacement is maintained by increasing the amount of mobile ions. The increase in mobile ions further improves the conductivity of the mobile ions in the solid electrolyte.

[0092] Furthermore, when the solid electrolyte according to the present embodiment contains a pentavalent or hexavalent metal element, for example, a part of the tetravalent metal element is replaced with a pentavalent or hexavalent metal element. As a result, the halogen ions (e.g., Cl) contained in the solid electrolyte are - ) are more strongly bound by the pentavalent or hexavalent ions. The mobile ions are less susceptible to electrical influence by the halogen ions, and therefore the mobile ions are more easily conducted within the solid electrolyte, resulting in an improved mobile ion conductivity of the solid electrolyte.

[0093] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. EXAMPLES

[0094] Example 1 [Preparation of solid electrolyte] The synthesis of solid electrolytes and the fabrication of solid electrolyte batteries were carried out in a glove box with circulating argon gas at a dew point of -99°C and an oxygen concentration of 1 ppm. In the glove box with the above environment, the raw powders LiCl and ZrCl4 were weighed out to a molar ratio of 2:1, placed in a Zr container with 5 mm diameter Zr balls, and subjected to mechanochemical milling using a planetary ball mill. The mixture was mixed for 50 hours while cooling at a rotation speed of 500 rpm, and then sieved through a 100 μm mesh sieve. This resulted in Li2ZrCl6 powder.

[0095] [Measurement of ionic conductivity] Next, in a glove box with argon gas circulating at a dew point of -99°C and an oxygen concentration of 1 ppm, the obtained Li2ZrCl6 powder was loaded into a pressure molding die and pressure molded at a pressure of 373 MPa to prepare a measurement cell for ionic conductivity.

[0096] The die for pressure molding is composed of a resin holder with a diameter of 10 mm, and upper and lower punches with a diameter of 9.99 mm made of electronically conductive SKD material (die steel). 110 mg of Li2ZrCl6 powder was filled into the die for pressure molding and molded at a pressure of 373 MPa using a press machine. The molded product is called the die after pressure molding.

[0097] After that, a stainless steel disk and a Teflon (registered trademark) disk, both 50 mm in diameter and 5 mm thick and with four screw holes, were prepared and the pressure molding die was set as follows. They were loaded in the following order: stainless steel disk / Teflon (registered trademark) disk / pressure molding die / Teflon (registered trademark) disk / stainless steel disk, and the four screws were tightened. Screws were also inserted into the screw holes on the sides of the upper and lower punches to serve as external connection terminals.

[0098] The external connection terminal was connected to a potentiostat equipped with a frequency response analyzer, and the ionic conductivity was measured using an electrochemical impedance measurement method. Measurements were performed at a frequency range of 7 MHz to 0.1 Hz, an amplitude of 10 mV, and a temperature of 25°C.

[0099] The measured ionic conductivity of the solid electrolyte of Example 1 was 5.0×10 -4 S / cm.

[0100] [XRD measurement] The obtained Li2ZrCl6 powder was filled into an XRD measurement holder in a glove box with argon gas circulating at a dew point of -99°C and an oxygen concentration of 1 ppm. The filled surface was then covered with Kapton tape (dried in vacuum at 70°C for 16 hours) to seal and protect against moisture, and the XRD measurement sample was prepared. The sample was then taken out into the atmosphere and XRD measurement was performed using an X-ray diffractometer (X'PertPro manufactured by PANalytical). Cu-Kα radiation was used as the X-ray source.

[0101] In addition, under the same conditions as the above XRD measurement, only the Kapton tape used for moisture prevention was attached to the XRD measurement holder, and background measurement was performed. Figure 2 shows the measured X-ray diffraction result of the Kapton tape.

[0102] FIG. 3 and FIG. 5 to FIG. 7 show the results of X-ray diffraction of the solid electrolyte according to Example 1. FIG. 3 shows the results of Example 9, Example 10, and Comparative Example 2, which will be described later. FIG. 5 shows the results of Example 2, Example 5, and Comparative Example 1, which will be described later. FIG. 6 shows the results of Example 14 and Example 16, which will be described later. FIG. 7 shows the results of Example 22 and Example 29, which will be described later. Note that, for the convenience of showing several types of Examples, they are shown in arbitrary units. The diffraction peaks in each Example were obtained by removing the background from the X-ray diffraction results measured in each Example.

[0103] For the solid electrolyte of Example 1, diffraction peaks were observed at 2θ=16.1°, 30.1°, 32.0°, 34.4°, 41.7°, 43.7°, 45.1°, 49.9°, 53.9°, 54.8°, 59.4, 60.7°, and 62.3°.

[0104] A graph showing the relationship between IB / IA and IC / IA is shown in Fig. 4. Fig. 4 is an enlarged view of the vicinity of a diffraction angle of 30° in Fig. 2. The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° and the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Example 1 was 0.195.

[0105] In addition, the ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° and the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 1 was 0.151.

[0106] Example 2 Example 2 differs from Example 1 in that aluminum chloride was added to the raw material powder. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.1:0.1:0.9. Li 2.1 Al 0.1 Zr 0.9 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0107] The ionic conductivity of the solid electrolyte according to Example 2 is 8.5×10 -4 S / cm.

[0108] The solid electrolyte of Example 2 had diffraction peaks at 2θ=16.1°, 30.0°, 32.0°, 34.4°, 41.7°, 43.6°, 44.9°, 49.8°, 54.2°, 54.6°, 59.4, 60.5°, and 62.4°.

[0109] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Example 2 was 0.187. The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 2 was 0.145.

[0110] Example 3 Example 3 differs from Example 1 in that aluminum chloride is added to the raw material powder, and the mixing ratio is different from Example 2. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.2:0.2:0.8. 2.2 Al 0.2 Zr 0.8 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0111] The ionic conductivity of the solid electrolyte according to Example 3 is 7.0×10 -4 S / cm.

[0112] The solid electrolyte of Example 3 had diffraction peaks at 2θ=16.1°, 30.0°, 32.0°, 34.4°, 41.7°, 43.6°, 44.9°, 49.8°, 54.2°, 54.6°, 59.4, 60.5°, and 61.9°.

[0113] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Example 3 was 0.347.

[0114] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 3 was 0.285.

[0115] Example 4 Example 4 differs from Example 1 in that aluminum chloride is added to the raw material powder, and the mixing ratio is different from Example 2. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.25:0.25:0.75. 2.25 Al 0.25 Zr 0.75 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0116] The ionic conductivity of the solid electrolyte according to Example 4 is 5.8×10 -4 S / cm.

[0117] The solid electrolyte of Example 4 had diffraction peaks at 2θ=16.1°, 30.0°, 32.0°, 34.4°, 41.7°, 43.6°, 45.0°, 49.9°, 54.2°, 54.6°, 59.0°, 60.5°, and 61.9°.

[0118] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 4 was 0.452.

[0119] In addition, the ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 4 was 0.372.

[0120] Example 5 Example 5 differs from Example 1 in that aluminum chloride is added to the raw material powder, and the mixing ratio is different from Example 2. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.3:0.3:0.7. 2.3 Al 0.3 Zr 0.7 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0121] The ionic conductivity of the solid electrolyte according to Example 5 is 5.1×10 -4 S / cm.

[0122] The solid electrolyte of Example 5 had diffraction peaks at 2θ=16.1°, 29.8°, 32.0°, 34.4°, 41.7°, 43.6°, 45.0°, 49.9°, 54.2°, 54.6°, 59.0°, 60.5°, and 61.9°.

[0123] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 5 was 0.549.

[0124] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 5 was 0.460.

[0125] Example 6 Example 6 differs from Example 1 in that aluminum chloride is added to the raw material powder, and the mixing ratio is different from Example 2. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.35:0.35:0.65. 2.35 Al 0.35 Zr 0.65 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0126] The ionic conductivity of the solid electrolyte according to Example 6 is 4.5×10 -4 S / cm.

[0127] The solid electrolyte of Example 6 had diffraction peaks at 2θ=16.1°, 29.8°, 32.0°, 34.4°, 41.7°, 43.6°, 45.0°, 49.9°, 54.2°, 54.6°, 59.0°, 60.5°, and 61.8°.

[0128] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 6 was 0.789.

[0129] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 6 was 0.647.

[0130] Example 7 Example 7 differs from Example 1 in that aluminum chloride is added to the raw material powder, and the mixing ratio is different from Example 2. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.4:0.4:0.6. 2.4 Al 0.4 Zr 0.6 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0131] The ionic conductivity of the solid electrolyte according to Example 7 is 4.1×10 -4 S / cm.

[0132] The solid electrolyte of Example 7 had diffraction peaks at 2θ=16.1°, 29.8°, 32.0°, 34.4°, 41.6°, 43.6°, 45.0°, 49.9°, 54.3°, 54.6°, 59.0°, 60.5°, and 61.8°.

[0133] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 7 was 1.290.

[0134] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 7 was 1.044.

[0135] Example 8 Example 8 differs from Example 1 in that aluminum chloride is added to the raw material powder, and the mixing ratio is different from Example 2. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.45:0.45:0.55. 2.45 Al 0.45 Zr 0.55 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0136] The ionic conductivity of the solid electrolyte according to Example 8 is 3.9×10 -4 S / cm.

[0137] The solid electrolyte of Example 8 had diffraction peaks at 2θ=16.1°, 29.7°, 32.0°, 34.4°, 41.6°, 43.6°, 44.9°, 49.4°, 54.3°, 54.6°, 59.0°, 60.5°, and 61.7°.

[0138] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 8 was 2.018.

[0139] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 8 was 1.578.

[0140] Comparative Example 1 Comparative Example 1 differs from Example 1 in that aluminum chloride is added to the raw material powder, and the mixing ratio is different from Example 2. The molar ratio of LiCl, AlCl3, and ZrCl4 was 2.5:0.5:0.5. 2.5 Al 0.5 Zr 0.5 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0141] The ionic conductivity of the solid electrolyte according to Comparative Example 1 is 3.4×10 -4 S / cm.

[0142] The solid electrolyte of Comparative Example 1 had diffraction peaks at 2θ=16.1°, 29.7°, 32.0°, 34.4°, 41.6°, 43.6°, 44.9°, 49.4°, 54.3°, 54.6°, 58.8°, 60.5°, and 61.7°.

[0143] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Comparative Example 1 was 3.026.

[0144] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Comparative Example 1 was 2.409.

[0145] Example 9 Example 9 differs from Example 1 in that the ratio of the raw material powders was changed. The molar ratio of LiCl to ZrCl4 was 2.2:0.95. 2.2 Zr 0.95 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0146] The ionic conductivity of the solid electrolyte according to Example 9 is 4.5×10 -4 S / cm.

[0147] The solid electrolyte of Example 9 had diffraction peaks at 2θ=16.0°, 30.0°, 32.0°, 34.4°, 41.6°, 43.6°, 44.9°, 49.7°, 54.2°, 54.7°, 59.4, 60.5°, and 62.1°.

[0148] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 9 was 0.239.

[0149] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 9 was 0.137.

[0150] Example 10 Example 10 differs from Example 1 in that the ratio of the raw material powders was changed. The molar ratio of LiCl to ZrCl4 was 2.4:0.9. 2.4 Zr 0.9 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0151] The ionic conductivity of the solid electrolyte according to Example 10 is 6.7×10 -4 S / cm.

[0152] The solid electrolyte of Example 10 had diffraction peaks at 2θ=16.1°, 29.9°, 31.9°, 34.5°, 41.6°, 43.6°, 44.8°, 49.8°, 54.2°, 54.7°, 59.4°, 60.5°, and 62.2°.

[0153] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 10 was 0.520.

[0154] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 10 was 0.342.

[0155] Example 11 Example 11 differs from Example 1 in that the ratio of the raw material powders was changed. The molar ratio of LiCl to ZrCl4 was 2.5:0.875. 2.5 Zr 0.875 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0156] The ionic conductivity of the solid electrolyte according to Example 11 is 7.1×10 -4 S / cm.

[0157] The solid electrolyte of Example 11 had diffraction peaks at 2θ=16.1°, 29.9°, 31.9°, 34.5°, 41.6°, 43.7°, 44.8°, 49.8°, 54.2°, 54.7°, 59.4°, 60.5°, and 62.2°.

[0158] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 11 was 0.873.

[0159] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 11 was 0.524.

[0160] Example 12 Example 12 differs from Example 1 in that the ratio of the raw material powders was changed. The molar ratio of LiCl to ZrCl4 was 2.6:0.85. 2.6 Zr 0.85 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0161] The ionic conductivity of the solid electrolyte according to Example 12 is 5.5×10 -4 S / cm.

[0162] The solid electrolyte of Example 12 had diffraction peaks at 2θ=16.1°, 29.9°, 31.9°, 34.5°, 41.6°, 43.7°, 44.7°, 49.8°, 54.2°, 54.7°, 59.4°, 60.5°, and 62.3°.

[0163] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 12 was 1.709.

[0164] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 12 was 0.962.

[0165] (Example 13) Example 13 differs from Example 1 in that the ratio of the raw material powders was changed. The molar ratio of LiCl to ZrCl4 was 2.7:0.825. 2.7 Zr 0.825 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0166] The ionic conductivity of the solid electrolyte according to Example 13 is 4.4×10 -4 S / cm.

[0167] The solid electrolyte of Example 13 had diffraction peaks at 2θ=16.1°, 29.8°, 31.9°, 34.4°, 41.6°, 43.7°, 44.7°, 49.7°, 54.2°, 54.7°, 59.4, 60.2, and 62.0°.

[0168] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 13 was 2.831.

[0169] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 13 was 1.540.

[0170] Comparative Example 2 Comparative Example 2 differs from Example 1 in that the ratio of the raw material powders was changed. The molar ratio of LiCl to ZrCl4 was 2.8:0.8. 2.8 Zr 0.8 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0171] The ionic conductivity of the solid electrolyte according to Comparative Example 2 is 3.6×10 -4 S / cm.

[0172] The solid electrolyte of Comparative Example 2 had diffraction peaks at 2θ=16.1°, 29.7°, 31.9°, 34.3°, 41.6°, 43.7°, 44.7°, 49.7°, 54.1°, 54.7°, 59.4, 60.1, and 61.7°.

[0173] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Comparative Example 2 was 4.522.

[0174] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Comparative Example 2 was 2.355.

[0175] Example 14 Example 14 differs from Example 1 in that yttrium chloride is added to the raw material powder. The molar ratio of LiCl, YCl3, and ZrCl4 is 2.1:0.1:0.9. Li 2.1 Y 0.1 Zr 0.9A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0176] The ionic conductivity of the solid electrolyte according to Example 14 is 5.8×10 -4 S / cm.

[0177] The solid electrolyte of Example 14 had diffraction peaks at 2θ=16.0°, 30.0°, 32.0°, 34.2°, 41.7°, 43.5°, 44.8°, 49.8°, 53.8°, 54.5°, 59.6°, 60.5°, and 62.5°.

[0178] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 14 was 0.213.

[0179] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 14 was 0.184.

[0180] Example 15 Example 15 differs from Example 1 in that yttrium chloride is added to the raw material powder, and the mixing ratio is different from Example 14. The molar ratio of LiCl, YCl3, and ZrCl4 was 2.2:0.2:0.8. Li 2.2 Y 0.2 Zr 0.8 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0181] The ionic conductivity of the solid electrolyte according to Example 15 is 6.6×10 -4 S / cm.

[0182] The solid electrolyte of Example 15 had diffraction peaks at 2θ=16.0°, 30.0°, 32.0°, 34.2°, 41.7°, 43.5°, 44.8°, 49.8°, 53.8°, 54.5°, 59.6°, 60.5°, and 62.5°.

[0183] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 15 was 0.318.

[0184] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 15 was 0.245.

[0185] (Example 16) Example 16 differs from Example 1 in that yttrium chloride is added to the raw material powder, and the mixing ratio is different from Example 14. The molar ratio of LiCl, YCl3, and ZrCl4 was 2.3:0.3:0.7. 2.3 Y 0.3 Zr 0.7 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0186] The ionic conductivity of the solid electrolyte according to Example 16 is 6.3×10 -4 S / cm.

[0187] The solid electrolyte of Example 16 had diffraction peaks at 2θ=16.0°, 29.8°, 31.8°, 34.1°, 41.7°, 43.5°, 44.8°, 49.7°, 53.8°, 54.5°, 59.6°, 60.4°, and 62.3°.

[0188] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 16 was 0.492.

[0189] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 16 was 0.348.

[0190] (Example 17) Example 17 differs from Example 1 in that yttrium chloride is added to the raw material powder, and the mixing ratio is different from Example 14. The molar ratio of LiCl, YCl3, and ZrCl4 was 2.4:0.4:0.6. 2.4 Y 0.4 Zr 0.6 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0191] The ionic conductivity of the solid electrolyte according to Example 17 is 5.5×10 -4 S / cm.

[0192] The solid electrolyte of Example 17 had diffraction peaks at 2θ=16.0°, 29.8°, 31.7°, 34.1°, 41.5°, 43.4°, 44.7°, 49.6°, 53.8°, 54.4°, 59.4, 60.3, and 62.1°.

[0193] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 17 was 0.841.

[0194] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 17 was 0.557.

[0195] (Example 18) Example 18 differs from Example 1 in that yttrium chloride is added to the raw material powder, and the mixing ratio is different from Example 14. The molar ratio of LiCl, YCl3, and ZrCl4 was 2.5:0.5:0.5. Li 2.5 Y 0.5 Zr 0.5 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0196] The ionic conductivity of the solid electrolyte according to Example 18 is 4.4×10 -4 S / cm.

[0197] The solid electrolyte of Example 18 had diffraction peaks at 2θ=15.9°, 29.7°, 31.6°, 34.1°, 41.4°, 43.4°, 44.7°, 49.6°, 53.8°, 54.4°, 59.2°, 60.2°, and 62.0°.

[0198] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 18 was 1.188.

[0199] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 18 was 0.748.

[0200] (Example 19) Example 19 differs from Example 1 in that yttrium chloride is added to the raw material powder, and the mixing ratio is different from Example 14. The molar ratio of LiCl, YCl3, and ZrCl4 was 2.6:0.6:0.4. Li 2.6 Y 0.6 Zr 0.4 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0201] The ionic conductivity of the solid electrolyte according to Example 19 is 3.8×10 -4 S / cm.

[0202] The solid electrolyte of Example 19 had diffraction peaks at 2θ=15.9°, 29.7°, 31.6°, 34.0°, 41.3°, 43.3°, 44.6°, 49.4°, 53.7°, 54.4°, 59.0, 60.2, and 61.9°.

[0203] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 19 was 2.218.

[0204] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 19 was 1.344.

[0205] Comparative Example 3 Comparative Example 3 differs from Example 1 in that yttrium chloride is added to the raw material powder, and the mixing ratio is different from Example 14. The molar ratio of LiCl, YCl3, and ZrCl4 was 2.7:0.7:0.3. 2.7 Y 0.7 Zr 0.3 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0206] The ionic conductivity of the solid electrolyte according to Comparative Example 3 is 3.4×10 -4 S / cm.

[0207] The solid electrolyte of Comparative Example 3 had diffraction peaks at 2θ=15.9°, 29.6°, 31.5°, 34.0°, 41.2°, 43.2°, 44.5°, 49.4°, 53.7°, 54.4°, 58.9, 60.1, and 61.7°.

[0208] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Comparative Example 3 was 3.533.

[0209] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Comparative Example 3 was 2.071.

[0210] (Example 20) Example 20 differs from Example 1 in that niobium chloride was added to the raw material powder. The molar ratio of LiCl, NbCl5, and ZrCl4 was 1.9:0.1:0.9. Li was produced by the mixing reaction of the raw material powder. 1.9 Nb 0.1 Zr 0.9 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0211] The ionic conductivity of the solid electrolyte according to Example 20 is 4.4×10 -4 S / cm.

[0212] The solid electrolyte of Example 20 had diffraction peaks at 2θ=16.1°, 30.0°, 32.0°, 34.4°, 41.7°, 43.6°, 44.9°, 49.8°, 54.1°, 54.6°, 59.4, 60.5, and 62.4°.

[0213] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 20 was 0.177.

[0214] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 20 was 0.104.

[0215] Example 21 Example 21 differs from Example 1 in that niobium chloride is added to the raw material powder, and the mixing ratio is different from Example 20. The molar ratio of LiCl, NbCl5, and ZrCl4 was 1.8:0.2:0.8. Li 1.8 Nb 0.2 Zr 0.8 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0216] The ionic conductivity of the solid electrolyte according to Example 21 is 5.0×10 -4 S / cm.

[0217] The solid electrolyte of Example 21 had diffraction peaks at 2θ=16.1°, 30.0°, 32.0°, 34.4°, 41.8°, 43.7°, 45.0°, 49.9°, 54.2°, 54.6°, 59.4, 60.5, and 62.4°.

[0218] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 21 was 0.169.

[0219] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 21 was 0.135.

[0220] Example 22 Example 22 differs from Example 1 in that niobium chloride is added to the raw material powder, and the mixing ratio is different from Example 20. The molar ratio of LiCl, NbCl5, and ZrCl4 was 1.7:0.3:0.7. Li 1.7 Nb 0.3 Zr 0.7 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0221] The ionic conductivity of the solid electrolyte according to Example 22 is 5.4×10 -4 S / cm.

[0222] The solid electrolyte of Example 22 had diffraction peaks at 2θ=16.2°, 30.1°, 32.1°, 34.3°, 41.9°, 43.9°, 45.1°, 49.9°, 54.2°, 54.7°, 59.5, 60.9, and 62.5°.

[0223] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 22 was 0.229.

[0224] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 22 was 0.180.

[0225] (Example 23) Example 23 differs from Example 1 in that niobium chloride is added to the raw material powder, and the mixing ratio is different from Example 20. The molar ratio of LiCl, NbCl5, and ZrCl4 was 1.6:0.4:0.6. Li 1.6 Nb 0.4 Zr 0.6 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0226] The ionic conductivity of the solid electrolyte according to Example 23 is 5.9×10 -4 S / cm.

[0227] The solid electrolyte of Example 23 had diffraction peaks at 2θ=16.2°, 30.1°, 32.1°, 34.3°, 41.9°, 43.9°, 45.1°, 50.0°, 54.2°, 54.7°, 59.5°, 60.9°, and 62.5°.

[0228] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 23 was 0.362.

[0229] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 23 was 0.257.

[0230] (Example 24) Example 24 differs from Example 1 in that niobium chloride is added to the raw material powder, and the mixing ratio is different from Example 20. The molar ratio of LiCl, NbCl5, and ZrCl4 was 1.5:0.5:0.5. Li 1.5 Nb 0.5 Zr 0.5 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0231] The ionic conductivity of the solid electrolyte according to Example 24 is 5.4×10 -4 S / cm.

[0232] The solid electrolyte of Example 24 had diffraction peaks at 2θ=16.2°, 30.1°, 32.1°, 34.3°, 41.9°, 43.9°, 45.1°, 50.0°, 54.2°, 54.7°, 59.5, 61.0, and 62.6°.

[0233] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 24 was 0.654.

[0234] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 24 was 0.429.

[0235] (Example 25) Example 25 differs from Example 1 in that niobium chloride is added to the raw material powder, and the mixing ratio is different from Example 20. The molar ratio of LiCl, NbCl5, and ZrCl4 was 1.4:0.6:0.4. Li 1.4 Nb 0.6 Zr 0.4 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0236] The ionic conductivity of the solid electrolyte according to Example 25 is 4.4×10 -4 S / cm.

[0237] The solid electrolyte of Example 25 had diffraction peaks at 2θ=16.2°, 30.2°, 32.2°, 34.2°, 42.0°, 43.9°, 45.1°, 50.0°, 54.3°, 54.7°, 59.5, 61.0, and 62.6°.

[0238] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 25 was 1.602.

[0239] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 25 was 1.007.

[0240] (Example 26) Example 26 differs from Example 1 in that niobium chloride is added to the raw material powder, and the mixing ratio is different from Example 20. The molar ratio of LiCl, NbCl5, and ZrCl4 was 1.3:0.7:0.3. Li 1.3 Nb 0.7 Zr 0.3 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0241] The ionic conductivity of the solid electrolyte according to Example 26 is 3.8×10 -4 S / cm.

[0242] The solid electrolyte of Example 26 had diffraction peaks at 2θ=16.3°, 30.2°, 32.2°, 34.2°, 42.0°, 44.0°, 45.2°, 50.1°, 54.4°, 54.7°, 59.6, 61.0, and 62.7°.

[0243] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 26 was 2.895.

[0244] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 26 was 1.763.

[0245] Example 27 Example 27 differs from Example 1 in that magnesium chloride was added to the raw material powder. The molar ratio of LiCl, MgCl2, and ZrCl4 was 2.1:0.05:0.95. Li was produced by the mixing reaction of the raw material powder. 2.1 Mg 0.05 Zr 0。95 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0246] The ionic conductivity of the solid electrolyte according to Example 27 is 5.5×10 -4 S / cm.

[0247] The solid electrolyte of Example 27 had diffraction peaks at 2θ=16.1°, 30.1°, 32.1°, 34.4°, 41.8°, 43.7°, 45.1°, 49.9°, 53.9°, 54.6°, 59.4, 60.7, and 62.3°.

[0248] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 27 was 1.191.

[0249] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 27 was 0.655.

[0250] (Example 28) Example 28 differs from Example 1 in that magnesium chloride is added to the raw material powder, and the mixing ratio is different from Example 27. The molar ratio of LiCl, MgCl2, and ZrCl4 was 2.2:0.1:0.9. Li 2.2 Mg 0.1 Zr 0。9 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0251] The ionic conductivity of the solid electrolyte according to Example 28 is 6.0×10 -4 S / cm.

[0252] The solid electrolyte of Example 28 had diffraction peaks at 2θ=16.1°, 30.2°, 32.1°, 34.4°, 41.8°, 43.7°, 45.1°, 49.8°, 54.0°, 54.6°, 59.4, 60.7, and 62.2°.

[0253] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 28 was 1.495.

[0254] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 28 was 0.838.

[0255] (Example 29) Example 29 differs from Example 1 in that magnesium chloride is added to the raw material powder, and the mixing ratio is different from Example 27. The molar ratio of LiCl, MgCl2, and ZrCl4 was 2.3:0.15:0.85. Li 2.3 Mg 0.15 Zr 0。85 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were performed. The X-ray diffraction results are shown in Figure 7. Note that, for the convenience of showing several examples, the results are shown in arbitrary units.

[0256] The ionic conductivity of the solid electrolyte according to Example 29 is 4.5×10 -4 S / cm.

[0257] The solid electrolyte of Example 29 had diffraction peaks at 2θ=16.1°, 30.3°, 31.9°, 34.4°, 41.8°, 43.7°, 45.1°, 49.8°, 54.1°, 54.6°, 59.3, 60.6, and 61.8°.

[0258] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 29 was 1.757.

[0259] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 29 was 1.008.

[0260] (Example 30) Example 30 differs from Example 1 in that magnesium chloride is added to the raw material powder, and the mixing ratio is different from Example 27. The molar ratio of LiCl, MgCl2, and ZrCl4 was 2.4:0.2:0.8. 2.4 Mg 0.2 Zr 0。8 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0261] The ionic conductivity of the solid electrolyte according to Example 30 is 4.3×10 -4 S / cm.

[0262] The solid electrolyte of Example 30 had diffraction peaks at 2θ=16.1°, 30.3°, 31.9°, 34.4°, 41.8°, 43.6°, 45.0°, 49.7°, 54.1°, 54.7°, 59.3, 60.6, and 61.8°.

[0263] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 30 was 2.177.

[0264] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 30 was 1.233.

[0265] (Example 31) Example 31 differs from Example 1 in that magnesium chloride is added to the raw material powder, and the mixing ratio is different from Example 27. The molar ratio of LiCl, MgCl2, and ZrCl4 was 2.6:0.3:0.7. 2.6 Mg 0.3 Zr 0。7 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0266] The ionic conductivity of the solid electrolyte according to Example 31 is 3.9×10 -4 S / cm.

[0267] The solid electrolyte of Example 31 had diffraction peaks at 2θ=16.1°, 30.3°, 31.9°, 34.4°, 41.7°, 43.6°, 45.0°, 49.7°, 54.2°, 54.7°, 59.2, 60.5, and 61.7°.

[0268] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 31 was 2.786.

[0269] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 31 was 1.552.

[0270] Comparative Example 4 Comparative Example 4 differs from Example 1 in that magnesium chloride is added to the raw material powder, and the mixing ratio is different from Example 27. The molar ratio of LiCl, MgCl2, and ZrCl4 was 2.8:0.4:0.6. 2.8 Mg 0.4 Zr 0。6 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0271] The ionic conductivity of the solid electrolyte according to Comparative Example 4 is 3.5×10 -4 S / cm.

[0272] The solid electrolyte of Comparative Example 4 had diffraction peaks at 2θ=16.0°, 30.2°, 31.8°, 34.5°, 41.7°, 43.5°, 45.0°, 49.7°, 54.2°, 54.7°, 59.2°, 60.5°, and 61.7°.

[0273] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Comparative Example 4 was 3.725.

[0274] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Comparative Example 4 was 2.053.

[0275] Comparative Example 5 Comparative Example 5 differs from Example 1 in that magnesium chloride is added to the raw material powder, and the mixing ratio is different from Example 27. The molar ratio of LiCl, MgCl2, and ZrCl4 was 3.0:0.5:0.5. 3.0 Mg 0.5 Zr 0。5 A powder of Cl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0276] The ionic conductivity of the solid electrolyte according to Comparative Example 5 is 3.0×10 -4 S / cm.

[0277] The solid electrolyte of Comparative Example 5 had diffraction peaks at 2θ=16.0°, 30.2°, 31.8°, 34.5°, 41.6°, 43.4°, 44.9°, 49.6°, 54.3°, 54.7°, 59.1°, 60.5°, and 61.7°.

[0278] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte according to Comparative Example 5 was 5.320.

[0279] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Comparative Example 5 was 2.919.

[0280] Comparative Example 6 Comparative Example 6 differs from Example 1 in that YCl3 was used as the raw material powder instead of ZrCl4. The molar ratio of LiCl to YCl3 was 3:1. 3.0 A powder of YCl6 was obtained. Other conditions were the same as in Example 1, and ion conductivity and X-ray diffraction were measured.

[0281] The ionic conductivity of the solid electrolyte according to Comparative Example 6 is 2.3 × 10 -4 S / cm.

[0282] The solid electrolyte according to Comparative Example 6 did not have diffraction peaks at 2θ=30.0°±0.5°, 2θ=32.0°±0.5°, or 2θ=34.4°±0.5°, and therefore IB / IA and IC / IA could not be calculated.

[0283] Example 32 Example 32 differs from Example 10 in that the mechanochemical milling treatment time was 20 hours, and other conditions were the same as in Example 10, and ion conductivity and X-ray diffraction were performed. Figure 8 shows the X-ray diffraction results for Examples 10 and 32. Li 2.4 Zr 0.9 A powder of Cl6 was obtained.

[0284] The ionic conductivity of the solid electrolyte according to Example 32 is 5.7×10 -4 S / cm.

[0285] The solid electrolyte of Example 32 had diffraction peaks at 2θ=16.0°, 29.9°, 32.0°, 34.6°, 41.7°, and 49.8°.

[0286] The ratio IB / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IB of the diffraction peak at 2θ=34.4°±0.5° of the solid electrolyte of Example 32 was 0.848.

[0287] The ratio IC / IA of the diffraction intensity IA of the diffraction peak at 2θ=32.0°±0.5° to the diffraction intensity IC of the diffraction peak at 2θ=30.0°±0.5° of the solid electrolyte shown in Example 32 was 0.799.

[0288] [Creating solid electrolyte batteries] The solid electrolyte batteries having the solid electrolytes of Examples 1 to 32 and Comparative Examples 1 to 6 were fabricated by the method described below, and the discharge capacity was measured by the method described below.

[0289] First, lithium iron phosphate (LiFePO4): each solid electrolyte of Examples 1 to 32 or Comparative Examples 1 to 6: acetylene black were weighed out to be 67:20:13 parts by weight and mixed in an agate mortar to prepare a positive electrode mixture.

[0290] Next, lithium titanium oxide (Li4Ti5O 12 ): The solid electrolytes of Examples 1 to 32 or Comparative Examples 1 to 6 and the carbon black were weighed out so that the ratio of the solid electrolyte to the carbon black was 68:20:12 parts by weight, and mixed in an agate mortar to prepare a negative electrode mixture.

[0291] A resin holder, a lower punch (also serving as a negative electrode current collector), and an upper punch (also serving as a positive electrode current collector) were prepared. A lower punch was inserted from below the resin holder, and 110 mg of the solid electrolyte of Examples 1 to 32 or Comparative Examples 1 to 6 was added from above the resin holder. Then, an upper punch was inserted on top of the solid electrolyte. This first unit was placed in a press machine, and a solid electrolyte layer was formed at a pressure of 373 MPa. The first unit was removed from the press machine, and the upper punch was removed.

[0292] Next, 10 mg of a positive electrode mixture was placed on the solid electrolyte layer (upper punch side) in the resin holder, the upper punch was inserted on top of it, the second unit was placed in the press, and molding was performed at a pressure of 373 MPa. Next, the second unit was removed, turned upside down, and the lower punch was removed. 11 mg of a negative electrode mixture was placed on the solid electrolyte layer (lower punch side), the lower punch was inserted on top of it, the third unit was placed in the press, and molding was performed at a pressure of 373 MPa. In this way, a battery element consisting of a positive electrode current collector / positive electrode / solid electrolyte / negative electrode / negative electrode current collector was produced.

[0293] After that, a stainless steel disk and a Teflon disk, each 50 mm in diameter and 5 mm thick and with four screw holes, were prepared, and the battery element was set as follows. They were stacked in the following order: stainless steel disk / Teflon disk / battery element / Teflon disk / stainless steel disk, and the four screws were tightened to create the third unit. Screws were inserted into the screw holes on the sides of the upper and lower punches as terminals for charging and discharging.

[0294] An A4-sized aluminum laminated bag was prepared as an exterior body for enclosing the fourth unit 4. An aluminum foil (width 4 mm, length 40 mm, thickness 100 μm) wrapped with maleic anhydride-grafted polypropylene (PP) as an external lead terminal and a nickel foil (width 4 mm, length 40 mm, thickness 100 μm) were thermally bonded to one side of the opening of the aluminum laminated bag at a distance so as not to cause a short circuit. The fourth unit was inserted into the aluminum laminated bag to which the external lead terminal was attached, and the screw on the side of the upper punch was connected to the aluminum terminal inside the exterior body and the screw on the side of the lower punch was connected to the nickel terminal inside the exterior body with lead wires. Finally, the opening of the exterior body was heat-sealed to form a solid electrolyte battery.

[0295] The charge and discharge test was carried out in a thermostatic chamber at 25°C. Charging was carried out at a constant current and constant voltage (CCCV) of 0.1C up to 4.2V. Charging was completed when the current was reduced to 1 / 20C. Discharging was carried out at 0.1C up to 3.0V. The results are shown in Table 1. The measurement results of Examples 1 to 32 and Comparative Examples 1 to 6 are summarized in Table 1.

[0296] [Table 1]

[0297] As shown in Table 1, the solid electrolytes of Examples 1 to 32 all had sufficiently high ionic conductivity. In addition, the solid electrolyte batteries having the solid electrolytes of Examples 1 to 32 all had sufficiently high discharge capacity.

[0298] (Consideration) Comparing Examples 1 to 32 with Comparative Examples 1 to 6, Examples 1 to 32 had a 3.5×10 -4 It can be seen that the ionic conductivity is higher than 1.0 S / cm.

[0299] It is seen that the solid electrolytes according to Examples 1 to 32 exhibit superior ion conductivity to the solid electrolytes according to Comparative Examples 1 to 6. It is considered that, compared to Comparative Example 6, Examples 1 to 32 and Comparative Examples 1 to 5 use compounds containing an alkali metal element, a tetravalent metal element, and a halogen element as main elements, which weakens the binding of the alkali metal by the halogen element, making mobile ions more mobile, and thus improves ion conductivity.

[0300] Moreover, the examples in which the values ​​of IB / IA and IC / IA were within the predetermined ranges had high ionic conductivity. As a result, as shown in FIG. 4, when the solid electrolyte had diffraction peaks at 2θ=30.0°±0.5°, 2θ=32.0°±0.5°, and 2θ=34.4°±0.5°, and the diffraction peak intensity at 2θ=32.0°±0.5° was greater than the other diffraction peak intensities, the ionic conductivity was improved. It is believed that the conductive path of mobile ions was secured by forming such a characteristic structure, which improved the ionic conductivity. [Explanation of symbols]

[0301] 1...Positive electrode, 1A...Positive electrode current collector, 1B...Positive electrode active material layer, 2...Negative electrode, 2A...Negative electrode current collector, 2B...Negative electrode active material layer, 3...Solid electrolyte layer, 10...Solid electrolyte battery

Claims

1. A compound containing an alkali metal element, a tetravalent metal element, and a halogen element as main elements, the compound has diffraction peaks at the positions of 2θ=32.0°±0.5°, 2θ=34.4°±0.5°, 2θ=43.7°±0.5°, 2θ=45.0°±0.5°, 2θ=54.2°±0.5°, 2θ=59.1°±0.5°, 2θ=60.5°±0.5°, and 2θ=62.2°±0.5° with respect to the wavelength of CuKα radiation, The compound is represented by the composition formula Li2+aMbZr1+cCl6+d, -1.5≦a≦1.5, 0≦b≦1.5, -0.7≦c≦0.2, and -0.2≦d≦0.2 are satisfied, M is one or more elements selected from Al, Ca, Nb, and Mg; A solid electrolyte, wherein a ratio IB / IA of a diffraction intensity IB of a peak having the strongest diffraction intensity at 2θ=34.4°±0.5° to a diffraction intensity IA of a peak having the strongest diffraction intensity at 2θ=32.0°±0.5° satisfies 0<IB / IA≦3.

2. A compound containing an alkali metal element, a tetravalent metal element, and a halogen element as main elements, the compound has diffraction peaks at the positions of 2θ=32.0°±0.5°, 2θ=30.0°±0.5°, 2θ=43.7°±0.5°, 2θ=45.0°±0.5°, 2θ=54.2°±0.5°, 2θ=59.1°±0.5°, 2θ=60.5°±0.5°, and 2θ=62.2°±0.5° with respect to the wavelength of CuKα radiation, The compound is represented by the composition formula Li2+aMbZr1+cCl6+d, -1.5≦a≦1.5, 0≦b≦1.5, -0.7≦c≦0.2, and -0.2≦d≦0.2 are satisfied, M is one or more elements selected from Al, Ca, Nb, and Mg; A solid electrolyte, wherein a ratio IC / IA of a diffraction intensity IC of a peak having the strongest diffraction intensity at 2θ=30.0°±0.5° to a diffraction intensity IA of a peak having the strongest diffraction intensity at 2θ=32.0°±0.5° satisfies 0<IC / IA≦2.

3. The compound has a wavelength of CuKα radiation of 2θ=16.1°±0.5°, 2θ=41.7°±0.5°, 2θ=49.9°±0.5°, The solid electrolyte according to claim 1 or 2, having diffraction peaks at the positions:

4. The compound has a wavelength of CuKα radiation of 2θ=30.0°±0.5°, 2θ=34.4°±0.5°, The solid electrolyte according to any one of claims 1 to 3, having diffraction peaks at the positions:

5. A solid electrolyte layer comprising the solid electrolyte according to any one of claims 1 to 4.

6. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, A solid electrolyte battery, wherein at least one of the positive electrode, the negative electrode, and the solid electrolyte layer comprises the solid electrolyte according to any one of claims 1 to 4.

7. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, A solid electrolyte battery, wherein the solid electrolyte layer comprises the solid electrolyte according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • All-solid lithium secondary battery

    JP2006244734A

  • All-solid battery and manufacturing method of all-solid battery

    JP2013257992A

  • Solid electrolyte material, and cell

    WO2018025582A1

  • Solid electrolyte material and battery

    WO2019135348A1

  • Halide solid electrolyte material and battery using same

    WO2020070955A1